2006
DOI: 10.1901/jaba.2006.134-05
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Fiction Writers' Productivity Through an Internet‐based Intervention

Abstract: Ten participants from an online community of fiction writers were exposed to a treatment package intended to increase their writing productivity. The package consisted of graphic feedback provided through a Web page, praise for goal completion delivered via e-mail, and editing of manuscripts by other members of the community dependent on the completion of word-count goals. A multiple baseline design across groups was used to evaluate the effects of the intervention, which was successful in increasing the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…In a politically related vein, bill-passing in the U.S. Congress is consistent with behavior often seen on a fixed-interval reinforcement schedule; that is, procrastination until just before the end of the session (Critchfield, Haley, Sabo, Colbert, & Macropoulis, 2003). On a very different note, the use of Internet-based goal setting, praise, graphic feedback, and peer editing produced increases in fiction writers' productivity over a 50-day intervention period (Porritt, Burt, & Poling, 2006).…”
Section: Community Involvement and The Environmentsupporting
confidence: 56%
“…In a politically related vein, bill-passing in the U.S. Congress is consistent with behavior often seen on a fixed-interval reinforcement schedule; that is, procrastination until just before the end of the session (Critchfield, Haley, Sabo, Colbert, & Macropoulis, 2003). On a very different note, the use of Internet-based goal setting, praise, graphic feedback, and peer editing produced increases in fiction writers' productivity over a 50-day intervention period (Porritt, Burt, & Poling, 2006).…”
Section: Community Involvement and The Environmentsupporting
confidence: 56%
“…Researchers in this area have used group analogs to single-subject designs (Ballard & Glynn, 1975;Glover & Gary, 1976;Brigham et al, 1972). Indeed, the multiple-baseline design replicated across groups (e.g., Porritt et al, 2006) could make fluencybased research feasible in university-level writing courses.…”
Section: Discussionmentioning
confidence: 99%
“…Among those resources, in the United States, are the dozen periodicals of The National Council of the Teachers of english (2007) and even a few articles published by behavior analysts. Behavior analysts have targeted such behaviors as spelling (Cuvo, Ashley, Marso, Zhang, & Fry, 1995); low number or rates of word or sentence production (Ballard & Glynn, 1975;Porritt, Burt, & Poling, 2006;Van Houten, Morrison, Jarvis, & McDonald, 1974 ); and aspects of writing, including creativity and originality (Glover, 1979) as well as quality (Ballard & Glynn, 1975;Van Houten et al, 1974). Behavior analytic treatment packages have included preparatory activities (Glover, 1979); timed and untimed practice (Cuvo et al, 1995;Glover & Gary, 1976;Van Houten et al, 1974); and, of course, consequences such as reinforcement and feedback (Ballard & Glynn, 1975;Brigham, Graubard, & Stans, 1972;Glover, 1979;Glover & Gary, 1976;Porritt et al, 2006).…”
mentioning
confidence: 99%
“…Online communities have been established for many business purposes. For example, online communities exist for fiction writers (Porritt et al, 2006) while O'Sullivan (2007) reported on the use of hosted Internet forums for the promotion of arts organizations. The latter contends these forums add value through informing, involving, and providing an interface for members.…”
Section: • Hedonicmentioning
confidence: 99%